The Impact of the Physical Environment on Children’s Experiences of Early Childhood Education - Ranathunga, Ruchikala (Auckland University of Technology, 2025)
This dissertation presents a critical integrative literature review examining the influence of the physical environment on children’s experiences in early childhood education (ECE), with a particular emphasis on the context of Aotearoa New Zealand. While pedagogy and teacher-child relationships remain central to early learning, this review focused on how elements such as spatial layout, aesthetics, sensory design, access to nature, and cultural visibility influence children’s holistic development, wellbeing, and sense of belonging. Framed by the research question, how does the physical environment impact children’s experiences in ECE? The review synthesised both international and local literature through the theoretical lenses of sociocultural theory, bioecological systems theory, and the principles of the New Zealand curriculum Te Whāriki (MoE, 2017). The findings highlight the uniquely diverse and bicultural context of Aotearoa New Zealand as central to understanding ECE settings and examine how historical developments, regulatory frameworks, and sector privatisation have contributed to wide variability in physical environments. Further, the review found that thoughtfully designed environments, characterised by environmental elements, support children’s cognitive growth, emotional regulation, social competence, spiritual expression, and identity formation. However, the literature also revealed significant challenges, including inequitable funding, regulatory constraints, and limited professional focus on spatial design and cultural responsiveness. Overall, the review concluded that physical environments must be recognised as active contributors to children's learning and development, with important implications for educators, policymakers, and centre designers. It offers actionable recommendations to promote equitable access to well-designed, flexible, and culturally sustaining environments. Finally, this work contributes to the ongoing discourse on environmental quality and its role in shaping more equitable and transformative early childhood education in Aotearoa New Zealand.